Regional and Ethnic Favoritism in the Allocation of Humanitarian Aid - Christian Bommer; Axel Dreher; Marcello Perez-Alvarez (Center for Economic Studies and ifo Institute (CESifo), 2018)
International humanitarian aid is pivotal in the response to natural disasters suffered by low-and middle-income countries. While its allocation has been shown to be influenced by donors' foreign policy considerations, power relations within recipient countries have not been addressed. This paper is the first to investigate the role of regional and ethnic favoritism in the formation of humanitarian aid flows. We construct a novel dataset combining information on birth regions of political leaders and the geographic distribution of ethnic groups within countries with high numbers of natural disasters building on census (IPUMS) and Demographic and Health Surveys (DHS) data. Our results suggest that the Office of US Foreign Disaster Assistance (OFDA) disburses larger amounts of aid when natural disasters affect the birth region of the countries' leader. We find some evidence that OFDA disburses aid more frequently to leaders' birth regions as well as when regions hit by disasters are populated by politically powerful or discriminated ethnicities. Our findings imply that humanitarian aid is not given for humanitarian reasons alone, but also serves elite interests within recipient countries.
Keywords: F35; 330; humanitarian aid; disasters; ethnic favoritism; regional favoritism